Updated list of the mosquitoes of Colombia (Diptera: Culicidae) - Rozo-Lopez, Paula (Biodivers Data J, 2015)
Abstract. BACKGROUND: A revised list of the mosquitoes (Diptera: Culicidae) known to occur in Colombia is presented. A total of 324 species from 28 genera of Culicidae are included. The species names are organized in alphabetical order according to the current generic and subgeneric classification, along with their authorship. The list is compiled in order to support mosquito research in Colombia. NEW INFORMATION: Our systematic review and literature survey found, by 16 February 2015, 13 records of culicid species previously overlooked by mosquito catalogs for Colombia: Anopheles costai da Fonseca & da Silva Ramos, 1939, An. fluminensis Root, 1927, An. malefactor Dyar & Knab, 1907, An. shannoni Davis, 1931, An. vargasi Galbadón, Cova García & Lopez, 1941, Culex mesodenticulatus Galindo & Mendez, 1961, Haemagogus capricornii Lutz, 1904, Isostomyia espini (Martini, 1914), Johnbelkinia leucopus (Dyar & Knab, 1906), Mansonia indubitans Dyar & Shannon, 1925, Psorophora saeva Dyar & Knab, 1906, Sabethes glaucodaemon (Dyar & Shannon, 1925), and Wyeomyia intonca Dyar & Knab, 1909. Moreover, Wyeomyia (Dendromyia) luteoventralis Theobald, 1901 is recorded for Colombia for the first time. This work provides important insights into mosquito diversity in Colombia, using the current nomenclature and phylogenetic rankings.